Perceived Service Quality, Not Accessibility, Drives Patient Satisfaction with Traditional Medicine: A Cross-Sectional Study at Bhutan's National Traditional Medicine Hospital - Karma Gaylek; Lobzang Dawa; Hendsun Hendsun (Open Access Indonesian Journal of Medical Reviews, 2026)
Background: Sowa Rigpa, Bhutan's traditional medicine system, is free at the point of use, yet the determinants of patient satisfaction remain poorly quantified. Objective: To determine which dimensions of the service experience predict overall satisfaction among repeat attenders at the National Traditional Medicine Hospital in Thimphu. Methods: This analytical cross-sectional study interviewed 209 patients aged 15–80 years with at least two previous attendances between 1 and 29 July 2025. A bilingual structured questionnaire assessed perceived service quality, accessibility and satisfaction (Cronbach's alpha 0.877). Associations were tested using Fisher's exact test with Benjamini–Hochberg correction. Result: Overall satisfaction was high in 88.3% of evaluable respondents (95% CI 83.1–92.1), including 98.1% for outpatient therapy and 93.9% for day-therapy massage, whereas perceived accessibility was high in 72.0%. Overall perceived quality was associated with satisfaction (p = 0.0014), as were perceptions of common services (p = 0.0001) and day-therapy massage (p = 0.0007); all survived correction. Accessibility was not associated with satisfaction (p = 0.3237). Poor accessibility was reported more often by men (OR 2.89, 95% CI 1.52–5.48), patients aged 35 years or under (OR 2.19, 95% CI 1.10–4.34) and better-educated patients (OR 2.81, 95% CI 1.27–6.20). Conclusion: Patient satisfaction at this national referral centre was driven by perceived care quality rather than accessibility. Privacy, waiting-area space and service hours are the main actionable priorities.